2022
DOI: 10.1063/5.0081117
|View full text |Cite
|
Sign up to set email alerts
|

Plasmonic enhancement in deep ultraviolet photoresponse of hexagonal boron nitride thin films

Abstract: Deep-ultraviolet (DUV) photodetectors based on hexagonal boron nitride ( h-BN) have demonstrated great potentials for various commercial and military applications; however, to date, most studies show that the h-BN photodetectors suffer from poor performance, such as low responsivity and large dark current. Herein, we report the dramatic enhancement of photoresponse in the DUV region of a h-BN device coupled with plasmonic nanostructures of either h-BN nanosheets (BNNSs) or Au nanoparticles (NPs). Large-area h-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…g) The semilogarithmic IV curves of the h‐BN photodetector with Au NPs under the dark and a 205 nm illumination at a power density of 19 mW cm −1 with the applied bias from −35 to 35 V. Reproduced with permission. [ 172 ] Copyright 2022, AIP Publishing. h) The dark currents of the h‐BN photodetector and h‐BN hybrid devices.…”
Section: H‐bn For Next‐generation Photonicsmentioning
confidence: 99%
See 1 more Smart Citation
“…g) The semilogarithmic IV curves of the h‐BN photodetector with Au NPs under the dark and a 205 nm illumination at a power density of 19 mW cm −1 with the applied bias from −35 to 35 V. Reproduced with permission. [ 172 ] Copyright 2022, AIP Publishing. h) The dark currents of the h‐BN photodetector and h‐BN hybrid devices.…”
Section: H‐bn For Next‐generation Photonicsmentioning
confidence: 99%
“…Zhu et al attempted to introduce plasmonic enhancement by incorporating Au NPs in the h-BN photodetector, which resulted in remarkable improvement of photoresponse. [172] The photocurrent of the h-BN photodetector with Au NPs was increased 7-9 times under 205 nm illumination due to the enhanced numbers of photoexcited electron-hole pairs (Figure 12g). Note that the antisymmetric current offset is induced since Au NPs are located only on one end as shown in the inset of Figure 12h.…”
Section: Impurity Dopingmentioning
confidence: 99%
“…channel limit, thickness/strain regulated physical attributes, flexible integratability, etc. Thus far, hundreds of 2DLMs spanning graphene, 7 transition metal dichalcogenides, [8][9][10] nitrides, 11 phosphides, 12 oxyhalides, 13 and Mxenes 14 have been developed for photodetection applications.…”
Section: Introductionmentioning
confidence: 99%
“…Since the revolutionary preparation of one-atom-thick graphene, 2D layered materials (2DLMs) have been established as one of the most promising material platforms toward realizing the next-generation integrated electronics, photonics and optoelectronics, 1–6 by virtue of the intriguing attributes spanning high light transmittance, excellent flexibility, wide-range properties, remarkable quantum confinement, ultra-scaled channel limit, thickness/strain regulated physical attributes, flexible integratability, etc. Thus far, hundreds of 2DLMs spanning graphene, 7 transition metal dichalcogenides, 8–10 nitrides, 11 phosphides, 12 oxyhalides, 13 and Mxenes 14 have been developed for photodetection applications.…”
Section: Introductionmentioning
confidence: 99%
“…However, the role of metal NPs on the performance of 2DLM-based UV PDs has rarely been explored. Recently, Zhu et al demonstrated an enhancement by nearly 7 times the response of deep-UV PDs fabricated on 200-nm-thick h-BN by utilizing Au NPs at a very high input voltage of 35 V. In addition, an enhancement in the current was observed only for the positive biases . Because deep-UV PDs fabricated on 2DLMs, particularly h-BN, can find a place in commercial applications in the coming years, there is a pressing need for detailed investigations of plasmonic-enhanced h-BN deep-UV PDs.…”
Section: Introductionmentioning
confidence: 99%